Biophysical and Biochemical Characterization of Nascent Polypeptide-Associated Complex of Picrophilus torridus and Elucidation of Its Interacting Partners - Singhal, Neelja; Sharma, Archana; Kumari, Shobha; Garg, Anjali; Rai, Ruchica; Singh, Nirpendra; Kumar, Manish; Goel, Manisha (Frontiers in Microbiology, 2020)
Nascent polypeptide-associated complex (NAC) is a ribosome-associated molecular chaperone which is present only in archaea and eukaryotes. The primary function of NAC is to shield the newly synthesized polypeptide chains from inappropriate interactions with the cytosolic factors. Besides, NAC has been implicated in diverse biological functions which suggest that it might be a multifunctional protein. An elaborate study on NAC can provide useful information on protein folding in the extreme conditions in which many archaea grow. Thus, in the present study, we have studied the biophysical and biochemical characteristics of NAC of Picrophilus torridus, an extreme thermoacidophilic archaeon. The study of protein-protein interactions and binding partners of a protein provides useful insights into the new/unreported roles of a protein. Thus, in this study we have identified the binding partners of NAC in P. torridus. The NAC protein of P. torridus was cloned, expressed and purified and, its binding partners were isolated by a pull down assay followed by identification with liquid chromatography mass spectrometry. To the best of our knowledge, this is the first report on biophysical and biochemical characterization of NAC from P. toridus and identification of its interacting partners.